HYDRAULIC STRUCTURES OF MIRZACHUL NATURAL AREA AND ITS IMPACT ON THE ENVIRONMENT - Sunnatillo Ibragimov (International Scientific and Current Research Conferences, 2021)
This article examines the morphometric dimensions of hydraulic structures built in the Mirzachul natural region and analyzes its impact on the environment.